Comparison of the Contents of Bioactive Compounds and Quality Parameters in Selected Mango Cultivars. Issue 6 (10th November 2013) - Sellamuthu, Periyar Selvam; Denoya, Gabriela Inés; Sivakumar, Dharini; Polenta, Gustavo Alberto; Soundy, Puffy
Abstract Mango cultivars Tommy Atkins, Zill, Peach, Sabre, Rosa and Phiva were analyzed for their quality parameters (fruit weight, flesh color chroma, L, h0, total soluble solid [TSS]/titratable acidity [TA], firmness), bioactive compounds (total phenols, carotenoids, ascorbic acid, antioxidant activity) and polyphenol oxidase (PPO) activity. Cv. Sabre showed highest total phenolic content (76.43 mg gallic acid/100 g FW), carotenoids (9.90 mg/100 g of FW), ascorbic acid content (69.71 mg/100 g of FW) and antioxidant activity (1.2 mg of gallic acid/g of FW), whereas cv. Peach mango contained lower bioactive compounds. Multivariate principal component analysis analysis showed higher concentration of bioactive compounds in cv. Sabre mango, whereas cv. Tommy Atkins was firm and heavier. Cv. Rosa and Phiva were moderately rich in bioactive compounds and lower in fruit weight and firmness, whereas cv. Peach was higher in TSS/ TA. The PPO activity was higher in cvs. Rosa and Zill. Practical Applications The variability in the quality parameters and bioactive components in five different mango cultivars was investigated. The results of this study provide valuable information to growers, distributors and consumers in selecting cultivars that are rich in bioactive components to consume as fresh fruit. Different cultivars were also identified for specific processing operations based on their quality parameters.